Age, class and race discrimination: their interactions and associations with mental health among Brazilian university students - Joao Luiz Bastos; Aluisio J. D. Barros; Roger Keller Celeste; Yin Paradies; Eduardo Faerstein (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
Although research on discrimination and health has progressed significantly, it has tended to focus on racial discrimination and US populations. This study explored different types of discrimination, their interactions and associations with common mental disorders among Brazilian university students, in Rio de Janeiro in 2010. Associations between discrimination and common mental disorders were examined using multiple logistic regression models, adjusted for confounders. Interactions between discrimination and socio-demographics were tested. Discrimination attributed to age, class and skin color/race were the most frequently reported. In a fully adjusted model, discrimination attributed to skin color/race and class were both independently associated with increased odds of common mental disorders. The simultaneous reporting of skin color/race, class and age discrimination was associated with the highest odds ratio. No significant interactions were found. Skin color/race and class discrimination were important, but their simultaneous reporting, in conjunction with age discrimination, were associated with the highest occurrence of common mental disorders.